The first-time manager's guide to team building - Topchik, Gary S. (AMACOM, 2007)
"Designed for immediate use by both you and your team members, the book covers team-building essentials, including decision making, goals and standards, honest communication, clear roles and responsibilities, and celebrating success. In addition, management expert Gary S. Topchik offers helpful activities and assessments and explains the five essential qualities of a high-performing team, providing you with indispensable, down-to-earth advice."--Jacket